Evaluation of CRISPR-Cas9 mismatch activity using a BRET-based reporter system - Wimmer, Tobias; Lorenz, Anthony; Hoßfeld, Lars; Goud Ponnam, Surya Prakash; Lytvynchuk, Lyubomyr; Stieger, Knut; Justus Liebig University Giessen (My University, 2025)
CRISPR-Cas has revolutionized molecular biology, offering unparalleled precision and versatility in genome editing. CRISPR-Cas, originally part of the bacterial immune system, allows for the targeted modification of specific DNA sequences within living organisms. Of the many CRISPR-Cas systems, Cas9 has been used most frequently and applications have reached clinical stage in rare diseases. The system uses single guide RNA molecules to direct the Cas9 enzyme to specific DNA sequences, where it induces double-strand breaks. However, CRISPR-Cas9 can tolerate single-base mismatches between the sgRNA and the target DNA, potentially leading to off-target effects and challenges in achieving precision in high fidelity editing. With the evaluation of mismatch repair activity of wild-type CRISPR-Cas9 using a bioluminescence resonance energy transfer (BRET) based reporter system and by leveraging the BRET’s sensitivity, we aim to quantify and characterize the cleavage events in mismatched sgRNA-Cas9/DNA interactions to predict off-target activity of a given sgRNA. This will improve the accuracy and reliability of CRISPR-Cas9 based genome editing. The robust reporter platform will enhance the refinement of CRISPR-Cas9 variants and facilitate the rational design of sgRNAs, ultimately improving the safety and efficacy of CRISPR-based therapeutic applications.
Keywords: ddc:610